Evaluation of Serum Uric Acid Levels in Pediatric Migraine Patients - Aydin, Hilal; Bicakcioglu, Isinsu; Bucak, Ibrahim Hakan; Orman, Aysen; Akkus, Mehmet (Klinische Pädiatrie, 2025)
This study examined serum uric acid levels in children with migraine compared to healthy controls, and explored links with gender and attack frequency.A retrospective analysis was conducted on pediatric migraine patients and controls seen between August 2019 and January 2025. Uric acid, Hb, Hct, iron, and TIBC levels were recorded.No significant difference in uric acid levels was found between groups or by attack frequency. However, male patients had higher uric acid levels than females (p=0.046). Other blood parameters were similar.Uric acid is not a reliable standalone marker for pediatric migraine, though gender differences suggest potential hormonal influences. Further research is needed.
Keywords: Migraine; Children; Uric acid; Level